Task-related activity in sensorimotor cortex in Parkinson's disease and essential tremor: changes in beta and gamma bands - Rowland, Nathan C.; de Hemptinne, Coralie; Swann, Nicole C.; Qasim, Salman; Miocinovic, Svjetlana; Ostrem, Jill; Knight, Robert T.; Starr, Philip A. (Frontiers in Human Neuroscience, 2015)
In Parkinson’s disease patients in the OFF medication state, basal ganglia local field potentials exhibit changes in beta and gamma oscillations that correlate with reduced voluntary movement, manifested as rigidity and akinesia. However, magnetoencephalography and low-resolution electrocorticography (ECoG) studies in Parkinson’s patients suggest that changes in sensorimotor cortical oscillations differ from those of the basal ganglia. To more clearly define the role of sensorimotor cortex oscillatory activity in Parkinson’s, we performed intraoperative, high-resolution (4 mm spacing) ECoG recordings in 10 Parkinson’s patients (2 females, ages 47-72) undergoing deep brain stimulation (DBS) lead placement in the awake, OFF medication state. We analyzed ECoG potentials during a computer-controlled reaching task designed to separate movement preparation from movement execution and compared findings to similar invasive recordings in eight patients with essential tremor (3 females, ages 59-78), a condition not associated with rigidity or akinesia. We show that 1) cortical beta spectral power at rest does not differ between Parkinson’s and essential tremor patients (p = 0.85), 2) early motor preparation in Parkinson’s patients in the OFF medication state is associated with a larger beta desynchronization compared to patients with essential tremor (p = 0.0061), and 3) cortical broadband gamma power is elevated in Parkinson’s patients compared to essential tremor patients during both rest and task recordings (p = 0.004). Our findings suggest an oscillatory profile in sensorimotor cortex of Parkinson’s patients that, in contrast to the basal ganglia, may act to promote movement to oppose the anti-kinetic bias of the dopamine-depleted state.